Analysis of a Combined-Type Axial-Flux Permanent Magnet Machine - Qiaoshan Li; Aimin Liu; Bingyi Zhang (IEEE Access, 2022)
A combined-type axial-flux permanent magnet machine is proposed in this paper. The structure of the proposed machine is introduced. The torque density characteristics of the proposed combined-type axial-flux permanent magnet machine are studied, and the torque density advantages of this kind of machine are analyzed by comparing with radial-flux permanent magnet machines. The magnetic field analysis method of the machine is studied. In the process of magnetic field analysis, an air gap permeance element is proposed to improve the traditional magnetic equivalent circuit method, which can facilitate the establishment of magnetic equivalent circuit model at different times. The calculation results of the proposed method are verified by finite element method. The cogging torque optimization of this machine is investigated, which includes magnet skewing with different reference modes. The optimal magnet skewing angle is calculated and verified, and the characteristics of different cogging torque optimization methods are summarized.